To determine which expression is NOT equivalent to \( 9x + 4y + 13 - 3x - y - 10 \), we will first simplify the original expression:
\[ 9x + 4y + 13 - 3x - y - 10 \]
Combining like terms:
-
Combine the \( x \) terms: \[ 9x - 3x = 6x \]
-
Combine the \( y \) terms: \[ 4y - y = 3y \]
-
Combine the constant terms: \[ 13 - 10 = 3 \]
Putting it all together, we get: \[ 6x + 3y + 3 \]
Now, we will evaluate each of the provided options to see if they simplify to \( 6x + 3y + 3 \).
A. \( 3(2x+y+1) \)
\[ 3(2x + y + 1) = 3 \times 2x + 3 \times y + 3 \times 1 = 6x + 3y + 3 \]
This is equivalent to \( 6x + 3y + 3 \).
B. \( 6x + 3(1+y) \)
\[ 6x + 3(1+y) = 6x + 3 \times 1 + 3 \times y = 6x + 3 + 3y \] This is equivalent to \( 6x + 3y + 3 \).
C. \( (9-3)x+(4-0)y+3 \)
\[ (9-3)x + (4-0)y + 3 = 6x + 4y + 3 \]
This is NOT equivalent to \( 6x + 3y + 3 \) (since the y-coefficient is different).
D. \( (13-10)+(9x-3x)+(4y-y) \)
\[ (13-10) + (9x-3x) + (4y-y) = 3 + 6x + 3y = 6x + 3y + 3 \]
This is equivalent to \( 6x + 3y + 3 \).
After evaluating all options, the expression that is NOT equivalent to \( 9x + 4y + 13 - 3x - y - 10 \) is:
\[ \boxed{C} \]